Presidential Address: Issuers, Underwriter Syndicates, and Aftermarket Transparency - GREEN, RICHARD C. (Journal of Finance, 2007)
ABSTRACT I model strategic interaction among issuers, underwriters, retail investors, and institutional investors when the secondary market has limited price transparency. Search costs for retail investors lead to price dispersion in the secondary market, while the price for institutional investors is infinitely elastic. Because retail distribution capacity is assumed to be limited for each underwriter‐dealer, Bertrand competition breaks down in the primary market and new issues are underpriced in equilibrium. Syndicates emerge in which underwriters bid symmetrically, with quantities allocated internally to efficiently utilize retail distribution capacity.